2012
DOI: 10.1109/tbme.2012.2182994
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization and Numerical Modeling of Tissue Electrical Conductivity during Pulsed Electric Fields for Irreversible Electroporation Treatment Planning

Abstract: Irreversible electroporation is a new technique to kill cells in targeted tissue, such as tumors, through a nonthermal mechanism using electric pulses to irrecoverably disrupt the cell membrane. Treatment effects relate to the tissue electric field distribution, which can be predicted with numerical modeling for therapy planning. Pulse effects will change the cell and tissue properties through thermal and electroporation (EP)-based processes. This investigation characterizes these changes by measuring the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 45 publications
4
116
1
1
Order By: Relevance
“…Our results were not entirely anticipated from the recent studies that have attempted to characterize electrical conductivity changes during IRE treatment in the kidney (11) and brain (32), including the use of finite element modeling (33). For the kidney, Neal et al noted (11) that electrical current values reached a plateau; whereas, we observed a decrease in current during the course of IRE treatment of the kidney.…”
Section: Experimental Studies: Irreversible Electroporation Ben-davidcontrasting
confidence: 69%
“…Our results were not entirely anticipated from the recent studies that have attempted to characterize electrical conductivity changes during IRE treatment in the kidney (11) and brain (32), including the use of finite element modeling (33). For the kidney, Neal et al noted (11) that electrical current values reached a plateau; whereas, we observed a decrease in current during the course of IRE treatment of the kidney.…”
Section: Experimental Studies: Irreversible Electroporation Ben-davidcontrasting
confidence: 69%
“…2,18,[27][28][29][31][32][33][34][35] Figure 2 shows the model geometry, a parallelepiped (eg, sizes 5 Â 3.5 Â 3.5 cm 3 ) with 2 cylinders that simulate the stainless steel needles, 1.2 cm long and 0.5 mm diameter. The gray parallelepiped represents a homogeneous material characterized by the electrical resistivity of the tissue in this example is 5 Ωm (conductivity of 0.2 S/m).…”
Section: Computational Modelmentioning
confidence: 99%
“…Accounting for dynamic conductivity allows for more accurate representation of lesions created by IRE (57), and potentially H-FIRE. Incorporating changes in tissue conductivity can be achieved using a fitted Gompertz function (58). Alternatively, a sigmoid function can mimic changes in electrical conductivity due to electric field magnitude as well as temperature.…”
Section: Ire and H-fire Treatment Planningmentioning
confidence: 99%